Widespread azendohsaurids (Archosauromorpha, Allokotosauria) from the Late Triassic of western USA and India. (10th December 2021) - Nesbitt, Sterling J.; Stocker, Michelle R.; Ezcurra, Martín D.; Fraser, Nicholas C.; Heckert, Andrew B.; Parker, William G.; Mueller, Bill; Sengupta, Saradee; Bandyopadhyay, Saswati; Pritchard, Adam C.; Marsh, Adam D.
Abstract: Archosauromorph reptiles underwent rapid lineage diversification, increases in morphological and body size disparity, and expansion into new adaptive landscapes. Several of the primary early archosauromorph clades (e.g. rhynchosaurs) are easy to differentiate from others because of their characteristic body types, whereas the more lizard‐like and carnivorous forms with long necks (e.g. tanystropheids) were historically all relegated to the groups Protorosauria or Prolacertiformes. However, it is now clear that these groups are polyphyletic and that a lizard‐like, carnivorous form is plesiomorphic for Archosauromorpha, and multiple subclades started with that body plan. Among these early forms is Malerisaurus from the Upper Triassic of India ( M. robinsonae ) and the Upper Triassic of south‐western USA ( M. langstoni ). In this paper, we critically re‐evaluate the genus. We find both species of Malerisaurus as valid, and identify Malerisaurus as an early diverging, but late‐surviving, carnivorous member of Azendohsauridae within Allokotosauria. Our histological analysis and assessment of ontogenetic changes of limb bones of small and large individuals demonstrate that the skeletons of the small forms grew slowly and became more robust through ontogeny, and that the larger recovered bones are at or near the maximum size of the taxon. Malerisaurus and Malerisaurus ‐like taxa were common members of the Otischalkian–Adamanian (late Carnian to mid‐Norian) faunal assemblages from Upper Triassic strata of the south western USA, but they are absent from the younger Revueltian holochronozone. Specimens from western North America show that Allokotosauria had a near‐Pangaean distribution for much of the Middle Triassic to Late Triassic.